Safety, Pharmacokinetics, Pharmacodynamics, and Plasma Lipoprotein Distribution of Eritoran (E5564) during Continuous Intravenous Infusion into Healthy Volunteers - Rossignol, Daniel P. (American Society for Microbiology, 2004)
Eritoran, a structural analogue of the lipid A portion of lipopolysaccharide (LPS), is an antagonist of LPS in animal and human endotoxemia models. Previous studies have shown that low doses (350 to 3,500 μg) of eritoran have demonstrated a long pharmacokinetic half-life but a short pharmacodynamic half-life. The present study describes the safety, pharmacokinetics and pharmacodynamics, and lipid distribution profile of eritoran during and after a 72-h intravenous infusion of 500, 2,000, or 3,500 μg/h into healthy volunteers. Except for the occurrence of phlebitis, eritoran administration over 72 h was safe and well tolerated. Eritoran demonstrated a slow plasma clearance (0.679 to 0.930 ml/h/kg of body weight), a small volume of distribution (45.6 to 49.8 ml/kg), and a relatively long half-life (50.4 to 62.7 h). In plasma, the majority (∼55%) of eritoran was bound to high-density lipoproteins. During infusion and for up to 72 h thereafter, ex vivo response of blood to 1- or 10-ng/ml LPS was inhibited by ≥85%, even when the lowest dose of eritoran (500 μg/h) was infused. Inhibition of response was dependent on eritoran dose and the concentration of LPS used as an agonist. Finally, in vitro analysis with purified lipoprotein and protein fractions from plasma obtained from healthy volunteers indicated that eritoran is inactivated by high-density but not low-density lipoproteins, very-low-density lipoproteins, or albumin. From these results, we conclude that up to 252 mg of eritoran can be safely infused into normal volunteers over 72 h and even though it associates extensively with high-density lipoproteins, antagonistic activity is maintained, even after infusion ceases.